The Role of Business Financial Reporting Assistance for SMEs in Cepogo Boyolali - Mangifera, Liana; Pratiwi, Diana Ayu; Muhammad, Rahardian (Journal of Community Services and Engagement: Voice of Community (VOC), 2024)
Training and support of SMEs' financial records are necessary so that entrepreneurs can have knowledge and skills in managing the financial management of each enterprise. The problem faced by SMEs Village Cepogo is the lack of financial management science that results in minimal knowledge and skills in SMEs financial management; no valid calculation of the value of the sale offered; no trace of SME's financial records. This dedication activity aims to improve knowledge and understanding of the management of SMEs Village Cepogo finance; to improve the skills management of the SMEs Village Cepogo financial; to enhance the effectiveness of the economy SMEs Town Cepogo. The solution to the problems implemented is to provide advice related to the management of SMEs Village Cepogo finance as well as to conduct training and support for the administration of SMEs Village Cepogo. The result of the accompaniment is that the participants have financial reports of the enterprise and can calculate the production costs to determine the selling price, this activity is followed with high enthusiasm by the SME actors who cooperate with BUMDES Cepogo.